Herdenking moord K.Duinmeijer. Opnamen voor Vrijheidsjournaal, aflevering 5: 'Kerwin, we zullen je nooit vergeten'
Herdenking moord K.Duinmeijer. Opnamen voor Vrijheidsjournaal, aflevering 5: 'Kerwin, we zullen je nooit vergeten'.